KONTRIBUSI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL ROLE PLAYINGUNTUK PENGEMBANGAN KETERAMPILAN INTELEKTUAL SISWA - Apriyanda Kusuma Wijaya; Urip Giyono; Muhammad Mona Adha (Universitas Tanjungpura, 2020)
This research aims to determine the effect of Civics Education using role playing models on students' intellectual skills. This research uses a quasi-experimental method with a quantitative approach. Overall Telkom Bandung Vocational School students become the study population then for the sample that is students of class X Multimedia-2 as an experimental class and class X Multimedia-3 as a control class. This research uses observation, tests, and questionnaires as research instruments. Processing and data analysis using test statistics T-parametric inferentialT-Test with the help of SPSS version 20 application software. The results of this research indicate that Civics Education using role playing models influences the development of students' intellectual skills. Students in classes using models role playing (experimental classes) have better intellectual skills than students in conventional learning classes lectures (control classes). Intellectual skills in this study include the ability to identify problems, describe problems, and take attitude towards problems. This is evidenced by the mean in the experimental class that is greater than the mean in the control class.Keywords : Intellectual Skills, Role Playing Model.